Review of life-cycle assessments of livestock production: Perspectives for application to environmental impact assessment in developing countries - Fraval, Simon; Lannerstad, Mats; Ran, Ylva; Notenbaert, An Maria Omer; Mugatha, Simon M.; Herrero, Mario (International Livestock Research Institute, 2015)
This review draws on Life-Cycle Assessments (LCA) of livestock value chains. The current state of livestock LCAs is summarized, with an emphasis on limitations and lessons for a developing country context. Of the 149 LCAs reviewed, 19 incorporated developing countries. Key messages are: LCAs can be conducted for livestock value chains in developing countries; and, lessons can be learnt to improve the rigor of alternative methodologies including modeling, indicator specification, allocation of impact and incorporating sensitivity analysis. Further, results from existing LCAs provide a point of reference for future LCAs and sustainability assessments in developing countries.